Strengthening Donor Trust via Enhanced Performance and Transparency in Zakat Management - Zarkasi, Muhammad Afandi; Sriyono, Sriyono (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Lazismu, an extension of Lembaga Amil Zakat, Infaq Sadaqoh Muhammadiyah, plays a crucial role in facilitating charitable donations and maintaining donor trust in the humanitarian sector. Specific Background: Despite its importance, Lazismu faces challenges regarding the management of zakat funds and transparency in financial reporting, which has led to diminished donor trust. Previous studies have inadequately explored the relationship between performance recognition and donor trust in zakat institutions. Knowledge Gap: This research aims to fill this gap by quantitatively examining how various independent variables—human resource performance enhancement, financial report transparency, and interpersonal communication within the fundraising division—impact donor trust at Lazismu in Mojokerto. Aims: The study specifically investigates the influence of these independent variables on donor trust in Lazismu, with a focus on enhancing organizational performance to regain donor confidence. Results: The findings reveal that enhanced human resource performance, transparent financial reporting, and improved interpersonal communication significantly contribute to increasing donor trust. Novelty: This research introduces a structured approach to evaluating zakat management performance through quantitative measures, offering insights into the dynamics of donor engagement and trust. Implications: The results underscore the necessity for zakat institutions to prioritize financial transparency and effective communication strategies to foster stronger relationships with donors, ultimately leading to increased zakat contributions and enhanced community support. Highlights: Trust Boost: Performance and transparency enhance donor confidence significantly. Engagement: Strong communication improves donor relationships and trust. Methodology: Quantitative research analyzes zakat institution performance effects. Keywords: Lazismu, donor trust, zakat management, financial transparency, interpersonal communication